Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.11113/jt.v79.9803
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Total Chlorine Free (Tcf) Bleaching on the Characteristics of Chemi Mechanical (Cmp) Pulp and Paper From Malaysian Durian (Durio Zibethinus Murr.) Rind

Abstract: Graphical abstract AbstractThe effects of bleaching process on the characteristics of pulp and paper produced from durian rind under chemi-mechanical pulping (CMP) method were investigated. All process and characteristic tests were conducted according to Malaysian International Organisation for Standardization (MS ISO) and Technical Association of the Pulp and Paper Industry (TAPPI). Three (3) stages of peroxide (P-P-P) bleaching sequence through the Total Chlorine Free (TCF) bleaching process were applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…It would be expected that this sample presented high deformations (Giacomozzi and Joutsimo 2017). However, the oxygen and ozone bleaching stage process promote a more intense degradation of polysaccharides and consequent loss of yield and pulp properties, such as decreased intrinsic viscosity and high fine content (Masrol et al 2017;Morais et al 2021a). The fiber length weight by length (FL) decreased over the PFI revolutions, contrary to the fiber width (FW), coarseness (C), and fines content (FC).…”
Section: Pulp Fiber and Structure Experimental Characterizationmentioning
confidence: 97%
“…It would be expected that this sample presented high deformations (Giacomozzi and Joutsimo 2017). However, the oxygen and ozone bleaching stage process promote a more intense degradation of polysaccharides and consequent loss of yield and pulp properties, such as decreased intrinsic viscosity and high fine content (Masrol et al 2017;Morais et al 2021a). The fiber length weight by length (FL) decreased over the PFI revolutions, contrary to the fiber width (FW), coarseness (C), and fines content (FC).…”
Section: Pulp Fiber and Structure Experimental Characterizationmentioning
confidence: 97%
“…Nevertheless, to the best of author's knowledge, there is a lack of research works and published articles on the utilization of durian rind as an alternatives pulp and paper material. In order to overcome this condition, chemi-mechanical pulping (CMP) of durian rind study has been explored in our previous study [26,27]. The findings of the study indicated that durian rind has bright potentials to be applied as a newly explored raw material for pulp and paper industry.…”
Section: Introductionmentioning
confidence: 99%